Disparities in Nurse Job Dissatisfaction and Intent to Leave: Implications for Retaining a Diverse Workforce. (June 2021) - Carthon, J. Margo Brooks; Travers, Jasmine L.; Hounshell, Danielle; Udoeyo, Idorenyin; Chittams, Jesse
Abstract : OBJECTIVE: To determine if Black nurses are more likely to report job dissatisfaction and whether factors related to dissatisfaction influence differences in intent to leave. BACKGROUND: Minority nurses report higher job dissatisfaction and intent to leave, yet little is known about factors associated with these differences in community settings. METHOD: Cross-sectional analysis of 11 778 nurses working in community-based settings was conducted. Logistic regression was used to estimate the association among race, job satisfaction, and intent to leave. RESULTS: Black nurses were more likely to report job dissatisfaction and intent to leave. Black nurses' intent to leave decreased in adjusted models that accounted for dissatisfaction with aspects of their jobs including salary, advancement opportunities, autonomy, and tuition benefits. CONCLUSION: Nurse administrators may find opportunities to decrease intent to leave among Black nurses through focused efforts to target areas of dissatisfaction.